Comparison of C-reactive protein and high-sensitivity C-reactive protein in acute appendicitis patients with normal white blood cells counts (Annals of Medical Research, 2022)
Aim: Acute appendicitis (AA) is one of the main causes of acute abdominal pain. The main goal of treatment is early diagnosis and emergency surgical intervention. Late diagnosis leads to complex acute appendicitis (gangrene, abscess, and perforation). Although the signs and symptoms of acute appendicitis are well known, it is sometimes difficult to diagnose. Various laboratory markers have been studied for the diagnosis of acute appendicitis, but none showed superiority over physical examination or imaging. In addition, the superiority of high-sensitivity C-reactive protein (hs-CRP) over C-reactive protein (CRP) in patients diagnosed with acute appendicitis has not been evaluated in any study to date. With the current study, we aimed to compare CRP and hs-CRP values ​​in patients with acute appendicitis whose white blood cells (WBC) are in the normal range.Materials and Methods: In this study, serum levels of CRP and hs-CRP were measured in 45 patients with acute appendicitis (who had normal WBC values) ​​and 42 healthy controls. The results obtained were statistically evaluated in terms of significant differences between the two study groups. In addition, ROC (Receiver Operating Characteristic) analysis was performed to determine the power of CRP and hs-CRP in the differential diagnosis of acute appendicitis.Results: CRP and hs-CRP levels of the patient group were significantly higher than the control group (0,002 and
Keywords: Acute appendicitis; C-reactive protein; High-sensitivity C-reactive protein